Exploring the Impact of Tourism on the Community's Economy: A Case Study of Tanjung Menangis Beach in Ketapang Village, East Lombok - Yudi Kusuma Hardi; I Wayan Nuada; Erri Supriyadi (Advances in Tourism Studies, 2023)
The purpose is to determine how the impact of the development of Tanjung Menangis Beach Tourist Destinations on the economic empowerment of local communities in the hamlet of Ketapang Village Peringgabaya Kbupaten East Lombok. The research method used in this study is the descriptive qualitative method. The data collected in this study comes from interviews, observations, and documentation from parties and institutions related to the development of tourism villages, namely business actors and craftsmen. the results of research in the field it is known that the form of Tourism Development in Tanjung Menangis Beach is in the form of infrastructure development both in terms of attractions, amenities, accessibility, ancillary services, and institutions have a positive impact on the economic empowerment of local communities. The research will be interesting to do because they want to know more about the tourist destination Tanjung Menangis Beach with various forms of development that have been done then how the impact of its development on the economic empowerment of local communities.